REMISSION OF SURGICAL HYPOPARATHYROIDISM POST ADRENALECTOMY FOR CUSHING'S SYNDROME - Loh , Ee Wen; Tan , Florence Hui Sieng (Journal of the ASEAN Federation of Endocrine Societies, 2022)
BACKGROUND Adrenal insufficiency (AI) is a well-recognized cause of hypercalcemia. In patients with hypoparathyroidism, the effect of coexisting AI on calcium level has not been well- described. CASE We report a case of a patient with hypoparathyroidism who was able to discontinue her long-term calcium and calcitriol replacement after adrenalectomy for Cushing’s syndrome. A 63-year-old female with post-operative hypopara- thyroidism after total thyroidectomy for papillary thyroid carcinoma (in 2005) was maintained on a stable dose of calcium carbonate 1 g BID and calcitriol 0.5 mcg BID. In 2015, she developed ACTH-independent Cushing’s syndrome and underwent right adrenalectomy for a 3.6 cm right adrenal adenoma. Post-operatively, she was diagnosed with AI [serum cortisol 1.04 μg/dl (NV: 5.27–22.45)] and was symptomatic of glucocorticoid withdrawal syndrome despite up-titration of hydrocortisone replacement to 35 mg daily. Interestingly, she was found to have hypercalcemia (highest corrected calcium level 2.97 mmol/L), necessitating down-titration and eventual total discontinuation of her calcium carbonate and calcitriol replacement. She remained normocalcemic despite being off calcium and calcitriol for 4 months. As her symptoms improved, oral calcium and calcitriol were slowly resumed at lower doses (calcium carbonate 500 mg BID and calcitriol 0.25 mcg OD) to maintain her calcium level. On follow-up, she still has AI [8 am serum cortisol 25.4nmol/L (NV: 133 – 537)] and requires 15 mg daily hydrocortisone replacement. CONCLUSION The pathophysiology of hypercalcemia in AI is incompletely understood. Our case supported a parathyroid- independent mechanism. In rare cases of AI with concurrent hypoparathyroidism, close monitoring of calcium levels is needed for medication dose adjustments to achieve normocalcemia.